2022
DOI: 10.13057/biodiv/d230244
|View full text |Cite
|
Sign up to set email alerts
|

Multiple antibiotic resistance and virulence factors of Staphylococcus aureus strains isolated from dairy farms in South Sulawesi, Indonesia

Abstract: Abstract. Juwita S, Indrawati A, Damajanti R, Safika, Mayasari NLPI. 2021. Multiple antibiotic resistance and virulence factors of Staphylococcus aureus strains isolated from dairy farms in South Sulawesi, Indonesia. Biodiversitas 23: 1015-1022. Antimicrobial resistance (AMR) is an important issue affecting human and animal health worldwide. This study aimed to investigate antibiotic resistance and determine the virulence factors of S. aureus isolated from the dairy farms in South Sulawesi, Indonesia. Thirty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
2
3
0
8
Order By: Relevance
“…Several studies have reported the production of hemolysins by S. aureus strains isolated from food sources. In agreement with the results of this study, a study by Juwita et al (2022) investigated the hemolysin production in S. aureus strains isolated from dairy products and human, and found that a signi cant proportion of the isolates produced hemolysin. The production of hemolysins by S. aureus strains of food origin has been associated with their ability to cause foodborne illnesses.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported the production of hemolysins by S. aureus strains isolated from food sources. In agreement with the results of this study, a study by Juwita et al (2022) investigated the hemolysin production in S. aureus strains isolated from dairy products and human, and found that a signi cant proportion of the isolates produced hemolysin. The production of hemolysins by S. aureus strains of food origin has been associated with their ability to cause foodborne illnesses.…”
Section: Discussionsupporting
confidence: 89%
“…In South Africa's Kariega estuary, 22 percent of S. aureus tetA genes were identified, similarly to the case with the tetA gene identified in this research [41], S. aureus strains obtained from Indonesian dairy farms in South Sulawesi Province all had the tetA gene [42]. In S. aureus, the tetA gene, in association with tetB, is necessary for the drug efflux pump that provides a significant amount of tetracycline resistance and is carried predominantly on a plasmid [43].…”
Section: Introductionsupporting
confidence: 77%
“…Antibiotic resistance pattern results show that all the isolates (100%) exhibited resistance to penicillin, and almost all were resistant to ampicillin (91.42%). is alarming rate of resistance to beta-lactam antibiotics is corroborated by some recent findings [54,55] and can be explained by the common use of β-lactams in the treatment of bovine mastitis [56]. A study carried out in Kenya by Mbindyo et al found that 71.4% of S. aureus strains exhibited resistance to ampicillin [57].…”
Section: Discussionmentioning
confidence: 85%